The Representation of Patriarchy in Indonesian Children Folk Tales from Sumatra Island - Dyani Masita Dewi (Bina Nusantara University, 2019)
This research aimed to discuss the topic of patriarchal research because it still existed in several countries in the world, especially Asia and more specifically, in Indonesia. This research was conducted to reveal how patriarchal values were reflected in Indonesian children’s folk tales from Sumatra Island. This research used a sociological approach to literature and used semiotic theory to analyze the data obtained. The researcher chose to use a qualitative descriptive method so that the analysis process could be described completely. The main data used in this research are several children’s folk tales originating from Sumatra Island, namely Province of North Sumatra (“Di Balik Derita Si Boru Tombaga”, “Bohong Merinang”, and “Si Kodok Kata Malem, Baik Budi Penawan Hati”), South Sumatra (“Langkuse dan Putri Rambut Putih”), and Jambi (“Legenda Bukit Perak”). This research finds that patriarchal values are represented in how women are associated with domestic works, women are considered as the subordinates and inferiors, as well as showing their dependence on men.